2020
DOI: 10.1111/evo.14152
|View full text |Cite
|
Sign up to set email alerts
|

Fitness effects of mutation in natural populations of Arabidopsis thaliana reveal a complex influence of local adaptation

Abstract: Little is empirically known about the contribution of mutations to fitness in natural environments. However, Fisher's Geometric Model (FGM) provides a conceptual foundation to consider the influence of the environment on mutational effects. To quantify mutational properties in the field, we established eight sets of MA lines (7‐10 generations) derived from eight founders collected from natural populations of Arabidopsis thaliana from French and Swedish sites, representing the range margins of the species in Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 87 publications
2
28
1
Order By: Relevance
“…To validate our predictive model of the mutation probability score, we used a second A. thaliana mutation accumulation experiment descended from eight founders collected in natural environments 50 . The lines were grown for seven to ten generations of single-seed descent before 150-bp paired-end read Illumina sequencing of pools of 40 seedlings.…”
Section: Methodsmentioning
confidence: 99%
“…To validate our predictive model of the mutation probability score, we used a second A. thaliana mutation accumulation experiment descended from eight founders collected in natural environments 50 . The lines were grown for seven to ten generations of single-seed descent before 150-bp paired-end read Illumina sequencing of pools of 40 seedlings.…”
Section: Methodsmentioning
confidence: 99%
“…The high f b values we observe (Fig 1) contradict the general expectation that beneficial mutations should be rare (32). However, many other studies – including with microbes and plants – have also reported a large number of beneficial mutations (3339). The large f b has been partially attributed to an improved ability to measure small-effect beneficial mutations (36, 40, 41) that are more common than expected (42), especially at low effective population sizes (38).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Fisher's Geometric Model (FGM) (Fisher 1930) predicts a higher absolute number (although not a higher frequency) of beneficial mutations when populations are far away from their adaptive peaks, such as in stressful or novel environments (Svensson and Berger 2019). Fisher's model is largely congruent with laboratory experiments and field studies on mutation accumulation (MA) lines, which have showed that mutation rates, fitness effects of novel mutations and mutational variances are highly context-and environment-dependent, and that fitness-effects of mutations are often larger in more stressful environments (Galhardo et al 2007;Rutter et al 2010;MacLean et al 2013;Weng et al 2021) An emerging view is therefore that evolution is not solely driven by the deterministic fitness-enhancing force of natural selection (Svensson and Berger 2019). Evolutionary biology today therefore recognizes historical contingencies such as the arrival order of mutations and mutational history (Losos et al 1998;Huey et al 2000;Svensson and Berger 2019), as exemplified in models of "mutation-order speciation" (Schluter 2009;Mendelson et al 2014).…”
Section: Introductionmentioning
confidence: 74%